PENERAPAN INKUIRI TERBIMBING PADA MATERI RANGKA DAN OTOT UNTUK MENINGKATKAN SIKAP PERCAYA DIRI PADA SISWA KELAS VIII.1 SMPN 1 TANJUNG BATU - Ardius Ahmad Kidan (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2015)
Abstract: In 2013, Indonesia has a new curriculum as a refinement of the previous curricula, Curriculum 2013 was prepared to prepare students who are not just smart cognitive, but also intelligent spiritual, emotional, and social, as well as be able to compete in any conditions. Reflection of the demands that the students emotionally and socially intelligent was evident in 2013 with the assessment curriculum on student attitude, confident attitude assessment is still difficult to come up with the students, from the observed data and the experience of teachers teaching in class VIII. 1. To enhance the confident attitude In the framework of learning materials and muscle in this study applied the method of guided inquiry as guided inquiry lead students to discover scientific concepts themselves so that they can formulate their own inventions with aplomb. This type of research is Classroom Action Research with research procedures as follows: planning the implementation of the action → action → reflection → observation → next cycle of action planning. Objectives to be achieved through this research are to: determine a confidence increase in grade VIII.1 SMPN1 Tanjung Batu on material of human skeletal and muscular with the application of guided inquiry learning model. The research instrument used in this study are: Observation sheet contains three indicators / aspects of confident attitude observed that: 1.berani presentation to the class, 2. Dare to argue, ask, or answer questions, 3. Opinion or do activities without hesitation -ragu. Data were analyzed quantitatively, to measure the percentage increase in the attitude of confidence for each indicator and the average percentage of confident attitude of the three indicators / aspects confidence in each cycle. The results of data analysis are then presented in the form of descriptive description. The indicator measures the success of the provision is if the average percentage of the value of three indicators / aspects of a confidence ≥ 75% (Good). Based on research data obtained from the third cycle of the average attitude score student responses from the three indicators / aspects are assessed confident attitude is 87.33%. Based on these results it is concluded that through guided inquiry learning model in the framework of material and human muscles can improve posture confidence VIII.1 grade students of SMP Negeri 1 Tanjung Batu.   Keywords: Guided Inquiry Learning Model, Attitude Confidence